Messing Up the Cancer Stem Cell Chemoresistance Mechanisms Supported by Tumor Microenvironment - Gaggianesi, Miriam; Di Franco, Simone; Pantina, Vincenzo Davide; Porcelli, Gaetana; D'Accardo, Caterina; Verona, Francesco; Veschi, Veronica; Colarossi, Lorenzo; Faldetta, Naida; Pistone, Giuseppe; Bongiorno, Maria Rita; Todaro, Matilde; et al. (Frontiers in Oncology, 2021)
Despite the recent advances in cancer patient management and in the development of targeted therapies, systemic chemotherapy is currently used as a first-line treatment for many cancer types. After an initial partial response, patients become refractory to standard therapy fostering rapid tumor progression. Compelling evidence highlights that the resistance to chemotherapeutic regimens is a peculiarity of a subpopulation of cancer cells within tumor mass, known as cancer stem cells (CSCs). This cellular compartment is endowed with tumor-initiating and metastasis formation capabilities. CSC chemoresistance is sustained by a plethora of grow factors and cytokines released by neighboring tumor microenvironment (TME), which is mainly composed by adipocytes, cancer-associated fibroblasts (CAFs), immune and endothelial cells. TME strengthens CSC refractoriness to standard and targeted therapies by enhancing survival signaling pathways, DNA repair machinery, expression of drug efflux transporters and anti-apoptotic proteins. In the last years many efforts have been made to understand CSC-TME cross-talk and develop therapeutic strategy halting this interplay. Here, we report the combinatorial approaches, which perturb the interaction network between CSCs and the different component of TME.